Fetal Echocardiography in Predicting Postnatal Outcome in Borderline Left Ventricle - Vorisek, Carina Nina; Bischofsberger, Lucy; Kurkevych, Andrii; Yürökür, Uygar; Wolter, Aline; Gembruch, Ulrich; Berg, Christoph; Hudel, Helge; Thul, Josef; Jux, Christian; Akintürk, Hakan; Schranz, Dietmar; Axt-Fliedner, Roland (Ultraschall in der Medizin - European Journal of Ultrasound, 2021)
Objectives Prenatal prediction of postnatal univentricular versus biventricular circulation in patients with borderline left ventricle (bLV) remains challenging. This study investigated prenatal fetal echocardiographic parameters and postnatal outcome of patients with a prenatally diagnosed bLV.Methods We report a retrospective study of bLV patients at four prenatal centers with a follow-up of one year. BLV was defined as z-scores of the left ventricle (LV) between –2 and –4. Single-ventricle palliation (SVP), biventricular repair (BVR), and no surgical or catheter-based intervention served as the dependent outcome. Prenatal ultrasound parameters were used as independent variables. Cut-off values from receiver operating characteristic curves (ROC) were determined for significant discrimination between outcomes.Results A total of 54 patients were diagnosed with bLV from 2010 to 2018. All were live births. Out of the entire cohort, 8 (15 %) received SVP, 34 (63 %) BVR, and 12 (22 %) no intervention. There was no significant difference with regard to genetic or extracardiac anomalies. There were significantly more patients with endocardial fibroelastosis (EFE) in the SVP group compared to the BVR group (80 % vs. 10 %), (p < 0.001). Apex-forming LV (100 % vs. 70 %) and lack of retrograde arch flow (20 % vs. 80 %) were associated with no intervention (p < 0.001). With respect to BVR vs. SVP, the LV sphericity index provided the highest specificity (91.7 %) using a cutoff value of ≤ 0.5.Conclusion The majority of bLV patients maintained biventricular circulation. EFE, retrograde arch flow, and LV sphericity can be helpful parameters for counseling parents and further prospective studies can be developed.
Keywords: congenital heart disease; borderline left ventricle; fetal echocardiography; hypoplastic left heart complex; prenatal diagnosis